2014
DOI: 10.1177/0363546514545856
|View full text |Cite
|
Sign up to set email alerts
|

Statins Enhance Rotator Cuff Healing by Stimulating the COX2/PGE2/EP4 Pathway

Abstract: Although chronic inflammation contributes to the development of tendinopathy, study results advocate for a positive role of PGE2 in tendon healing during the acute inflammatory phase that follows tendon surgical repair. It is therefore suggested that ATV should be further investigated as a possible modality to improve tendon healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
(37 reference statements)
3
48
0
2
Order By: Relevance
“…In the present study, we find that all six statins are able to decrease PGE2 at lower concentrations; however, at the maximal concentration (100  μ M), PGE2 release was either unaffected or elevated beyond LPS induction alone. Statin-induced increases in PGE2 production have been reported in nonneurological models, although these have been in models of acute in vivo inflammation via experimental rotator cuff injury [69]. Again, further investigation may be warranted to clarify whether the observations from the present study are due to dose-dependent effects.…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, we find that all six statins are able to decrease PGE2 at lower concentrations; however, at the maximal concentration (100  μ M), PGE2 release was either unaffected or elevated beyond LPS induction alone. Statin-induced increases in PGE2 production have been reported in nonneurological models, although these have been in models of acute in vivo inflammation via experimental rotator cuff injury [69]. Again, further investigation may be warranted to clarify whether the observations from the present study are due to dose-dependent effects.…”
Section: Discussionmentioning
confidence: 73%
“…A previous in vitro study has shown that the cells appear to arrest in the G1-phase of the cell cycle when treated with simvastatin, an effect that could be reversed by mevalonate or two down-stream intermediates [18]. There are however also studies which show no effect on proliferation by treatment with lovastatin [17] or even a higher proliferation with atorvastatin treatment [13]. The discrepancy between these results could perhaps be a question of timing or dosage.…”
Section: Discussionmentioning
confidence: 99%
“…However, statin treatment during tendon or ligament healing appears to have a positive effect [1315], especially on tendon to bone healing [13, 15]. Statins have been suggested to destabilize cell membranes, lead to tenocyte apoptosis or disturb matrix remodeling through an altered expression and activity of MMPs and collagens [8, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with sickle cell disease can develop oxidative stress and chronic inflammation to their distal vasculature as a result of transient vaso-occlusion and subsequent [196][197][198] Decrease decline in GFR Prevent contrast induced acute kidney injury Decrease risk of stroke Fracture injuries, bone healing, & osteoporosis [199][200][201][202][203][204] Promote mesenchymal cell differentiation to osteoblasts Protect osteoblasts from apoptosis Reduce osteoclast activity and bone resorption HIV [205][206][207][208][209][210][211] Slow progression of vascular disease on ART Improve flow-mediated vasodilation Implement immunomodulation Reduce all-cause mortality Immunomodulation [212][213][214] Inhibit interferon production Decrease T cell activation Infection [215][216][217][218] Reduce risk of mortality from bacterial and viral infection Lupus [219][220][221][222] Reduce C-reactive protein Reduce circulating chemokines Improve endothelial function Polycystic ovary syndrome [223][224][225] Reduce markers of inflammation Reduce androgenic steroid concentrations Rheumatoid arthritis [226][227][228][229][230][231] Reduce risk of mortality Reduce joint pain/swelling Reduce markers of inflammation Rotator cuff injury 232,233 Stimulate migration and adhesi...…”
Section: Future Considerationsmentioning
confidence: 99%